Implementing an Interactive Introduction to Complementary Medicine for Chronic Pain Management Into the Medical School Curriculum - Uttara Gadde; Pravin Matthew; Raagni Kumar; Rashi Aggarwal; Michelle Dalla Piazza; Sangeeta Lamba (Association of American Medical Colleges, 2020)
Introduction In the setting of the opioid crisis, chronic pain management requires new approaches and open dialogue between physicians and patients to explore evidence-based nonpharmacologic treatments. We developed an educational session on the role of complementary and alternative medicine (CAM) for chronic pain management as part of our larger curriculum on health equity and social justice. Methods Students and faculty developed a novel educational session for second-year medical students consisting of a lecture and an experiential small-group session immersing the students in CAM. We conducted pre- and postsurveys to assess the students' self-reported learning and impressions of the session. Results Over the academic years of 2018-2019 and 2019-2020, 345 second-year medical students participated in this mandatory session. In matched pre-and postsession surveys, students rated their knowledge of the evidence behind CAM practices, and reported statistically significant increases in their understanding. When asked about the importance of physician familiarity with common CAM practices, students noted both a high baseline agreement and a statistically significant increase after the session concluded. Familiarity with financial costs of each of the practices also saw statistically significant increases after the session. Discussion Our results indicated that the session met the educational objectives. A critical part of improving our session between academic years involved gathering feedback and implementing changes based on these suggestions. Our model is easy to implement and replicate at medical schools across the country. Future studies should assess the effects of CAM-focused educational interventions on practices in the clinical setting.